PrEP Use Awareness and Interest Cascade among MSM and Transgender Women Living in Bali, Indonesia - Cempaka, Rissa (Trop Med Infect Dis, 2020)
Indonesia has not implemented HIV pre-exposure prophylaxis (PrEP) despite global calls for its scale-up, and there is limited information about attitudes towards PrEP among its potential users. We aim to present a PrEP cascade among men who have sex with men (MSM) and transgender women (known locally as “waria”) in Denpasar, Bali, from a cross-sectional survey with 220 HIV-negative MSM/waria recruited from one clinic in Denpasar. Only 16.4% of participants had heard of PrEP before. From first-to-last steps included in the cascade, we found 77.3% (170/220) of participants were classified with HIV high risk, 75.9% (129/170) perceived themselves as being at high risk, 81.4% (105/129) expressed interest in using PrEP, 78.1% (82/105) were willing to do PrEP procedures, 48.8% (40/82) were willing to pay 500,000–600,000 IDR, and only two participants had ever been on PrEP before (5.0% of those willing to pay and 0.9% of the total sample). Multivariate logistic regression analysis showed that self-perception of high HIV risk was lower among older age groups (p < 0.001 among 30–39; p = 0.002 among > 40) and higher among participants with multiple sex partners (p = 0.016). Interest in using PrEP was lower among participants with high social engagement as MSM/waria (p = 0.002) and was higher among participants with multiple sex partners (p = 0.020) and inconsistent condom use (p = 0.011). This study has shown a significantly low level of PrEP awareness among its participants and decreases in interest in PrEP use due to procedure and cost. It suggested that an appropriate PrEP campaign is needed if PrEP is going to be introduced in Indonesia.